Рецидивне злоякісне лентиго: консервативне лікування іміквімодом чи повторне хірургічне видалення? Тривале спостереження: випадок з практики - De Giorgi, V.; Zuccaro, B.; Silvestri, F.; Venturi, F.; Colombo, J.; Trane, L. (PH Akademperiodyka, 2023)
A case of recurrent lentigo maligna in a 45-year-old woman is presented. The disease relapsed several times following the surgical excision of the lesion. An alternative treatment with imiquimod 5% cream was then used. After 4 years of follow-upfrom the last surgery, this treatment achieved total clearance of the lesion. The problems of lentigo maligna diagnosis and treatment are discussed.